Enhanced antinociceptive effects of mitragynine in combination with morphine via opioid receptors activation - Abdul Rahman, Shamima (2014)
The management of chronic pain is one of the greatest challenges in modern medicine. Opiates such as morphine have been used to treat pain for centuries. However, the long term use of morphine is limited due to its side-effects. To date, a number of natural compounds have been detected to possess analgesic effects. One of these natural compound is mitragynine (MG) which is isolated from Mitragyna speciosa Korth. Mitragyna speciosa is popularly known as ‘ketum’ in Malaysia and ‘kratom’ in Thailand. Over 25 alkaloids are found in Mitragyna speciosa, MG being a major one. In this study, we investigated the action of MG as antinociceptive agent and the receptor selectivity effect. The nociceptive effect was estimated in a hot plate test (Ugo Basile model 7280; 50.0 ºC). The latency time was estimated until the mice showed pain responses such as shaking, licking or jumping and the duration of latency was measured for every 15 minutes until 120 minutes. Male ICR mice (n=8/group) were administered intraperitoneally with single dosage of MG (3, 10, 15, 30, and 35 mg/kg), 15 minutes prior to pain induction. The control groups were given appropriate dose of vehicle. For the receptor selectivity test, the treated groups were administered naloxone (non-selective opioid antagonist), naltrindole (δ-opioid antagonist), norbinaltorpimine (κ-opioid antagonist) and AM251 (cannabinoid 1 antagonist) respectively prior to MG injection at the dosage of 35 mg/kg. The groups administered with MG showed an increased in latency time as compared to the control groups in a dose-dependent manner. Meanwhile, 35 mg/kg of MG was found to significantly increase the latency time. The results also showed that naloxone and naltrindole fully blocked the antinociceptive effect of MG, whilst norbinaltropimine partially blocked the effect, but the antinociceptive effect of MG was not antagonized by AM251. These results demonstrated that MG acts through opioid receptor specifically on δ and κ receptor and not through the cannabinoid CB1 receptor. Later on, we investigated the enhancement of analgesic action of this compound when combined with morphine and the effect on the development of tolerance due to morphine acutely and chronically. Male ICR mice (n=7/group) were administered intraperitoneally with a single dose of MG either 15 mg/kg or 25 mg/kg combined with morphine (5 mg/kg) in the acute study, whilst the study was continued for 9 days for the chronic phase. The control groups were given the appropriate dose of a vehicle. The antinociceptive effect was estimated with a hot plate test (Ugo Basile model 7280; 50.0 ºC). The latency time was assessed until the mice showed a pain response such as shaking, licking or jumping. The expression of cAMP, cAMP response element binding (CREB) protein, ERK and c-fos were analyzed. Liver and kidney function test were also analyzed and compared between groups. In acute study, the administration of MG and morphine showed a significant latency period compared to the vehicle treated groups. The combination of MG and morphine has enhanced morphine-induced analgesia which shows synergism in analgesic action. In the chronic phase, the concurrent administration of MG and morphine showed a significant increase in the latency time when compared to morphine alone groups and the remarkable analgesic effects in the combination regimens were maintained from day 1 until day 9. The result was in contrast when compared to morphine alone groups, where the latency time were reduced from day 5 to day 9. For the protein expressions, there were a significant increment of the cAMP and CREB levels (p<0.001) in groups treated with 5 mg/kg morphine but there was no significant changes of cAMP and CREB expression for MG alone groups and groups combined with morphine. There were no significant changes in other proteins (ERK and c-fos) for all groups when compared with the control group. There was also no significant changes in the liver enzymes of the treated groups when compared to the control group except for the AST level. There were no significant changes in the excretion level of urea in all groups when compared to the control groups. Similar results were found for the excretion of creatinine. However, the creatinine excretion was significantly increased when the treatment was combined. This study indicates that MG has antinociceptive properties and act fully via the opioid system. It also indicates that concurrent administration of morphine and MG enhanced the analgesic effects. Following the inclusion of MG, tolerance due to repeated administration of morphine is delayed.